ÙØ¹Ø§Ù„ÙŠØ© Ù„Ø¹Ø¨Ø© ØªØ®Ù…ÙŠÙ† Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù„ØªØ±Ù‚ÙŠØ© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ù…Ø¹Ù„Ù…Ø§Øª Ù†Ù‡Ø¶Ø© Ø§Ù„ÙˆØ·Ù† Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙ†Ø´ÙˆØ± - Hauliyatu Sahrah; Muhammad Ihsan; Suaidi Suaidi (Lughatu Ad-dhat, 2022)
The purpose of this research is to find out whether using a guessing game method can improve Arabic vocabulary in Nahdat Al-Watan Islamic Middle School Teachers Venture. The type of research used in this research is a quantitative research that consists of two chapters: the experimental group and the implementation control group, the experimental group with 26 students, the control group with 26 students, the control group and the experimental group with 52 students. The results showed that the learning that took place using the guessing game method in the eighth semester of the Arabic language was very successful because in this research there was an increase and the indicators of success were achieved. The results of this research are that there is a comparison between the learning outcomes of the experimental class students, which were observed from the post-test score with an average value of 88,70. And the degree of dimensional control with an average value of 23.69. There is a difference in the students' learning outcomes with a value of 2,008 thitung, 3,874 ttabel > at a significant level of 5%, which indicates that there is a difference between the value of the experimental class and the value of the control class. The value of the pre-test for the experimental group is 58,70, and the value of the post-test for the experimental group is 88,77. From the results of this research, it was concluded that there appears to be an improvement in the vocabulary of Arabic among the eighth grade students in the Nahdat Al-Watan Islamic Intermediate School Teachers Venture. Keywords: the game of guessing words and the Arabic language